2019
DOI: 10.11591/ijece.v9i2.pp1045-1057
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic control for optimal power flow in islanded microgrid

Abstract: <p>The problem of optimal power flow (OPF) in an islanded mircrogrid (MG) for hybrid power system is described. Clearly, it deals with a formulation of an analytical control model for OPF. The MG consists of wind turbine generator, photovoltaic generator, and diesel engine generator (DEG), and is in stochastic environment such as load change, wind power fluctuation, and sun irradiation power disturbance. In fact, the DEG fails and is repaired at random times so that the MG can significantly influence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the unit-commitment formulation, a stochastic approach is used, particularly, the authors in [7] report about the use of scenarios for generation with distribution probability functions, the demand is considered constant. Formulations with a stochastic approach has been suggested to manage wind power uncertainty in power system operation [8][9][10][11] and in microgrids in [12]. The flexibility in power system operation will be a critical issue under high penetration of wind power to deal with uncertainty and intermittency.…”
Section: Introductionmentioning
confidence: 99%
“…In the unit-commitment formulation, a stochastic approach is used, particularly, the authors in [7] report about the use of scenarios for generation with distribution probability functions, the demand is considered constant. Formulations with a stochastic approach has been suggested to manage wind power uncertainty in power system operation [8][9][10][11] and in microgrids in [12]. The flexibility in power system operation will be a critical issue under high penetration of wind power to deal with uncertainty and intermittency.…”
Section: Introductionmentioning
confidence: 99%
“…Two main approaches were suggested for microgrids control: centralized and distributed control. Centralized control has been extensively used in literature for both AC and DC microgrids control [3][4][5][6][7][8][9][10][11][12][13] including secondary control [3][4][5] and power management [6][7][8] among others [9][10][11][12][13]. Distributed control is a modern control approach developed as a natural solution for the naturally distributed systems as a more reliable control strategy, since the control is geographically distributed along with the system.…”
Section: Introductionmentioning
confidence: 99%
“…In [17], the energy storage systems and DR are introduced to the traditional scheduling model of wind and thermal power with carbon emission trading for reducing the influence of random nature of wind power on system operation. From the above literature review, it can be observed that there is a pressing requirement for an optimal operation of MG considering the RESs, BES systems, EVs and DR [18][19][20].…”
Section: Introductionmentioning
confidence: 99%